Process approach in teaching of ESL writing: teacher's assitance and its practicality in real classroom - Jalaludin, Ilyana (Sage Publications, 2019)
Writing in a first and second language are two different contexts and involve significant different composing process. In general, most ESL students have difficulties in the rhetorical and linguistics aspects of writing because of their prior education and education backgrounds (Mengjie Wei, 2017:16). Given the complexity of writing tasks, it is not surprising that L2 writers may experience various writing difficulties ranging from mechanical up to the content or idea development level. Although writing is teachable, the conversion of thought into written form is a difficult activity that requires organized pedagogical approaches and complementary skills. This is a case study which discusses the practices of process approach in teaching ESL writing and its practicality. The findings were based on a long-term observation and interview of three form 4 students and a teacher in Malaysia rural area school. Students’ writings were analysed to show the students’ development when activities based on Process approach were implemented. Findings managed to identify five different techniques used by the teacher in trying to implement process approach in writing. This process process managed to show the students the fallacy of assuming too much in writing and the need to provide more detail, or where they were being repetitious of ideas and get off the track. Changes could be seen in terms of words and elaboration in the second draft throughout the learning process until the compositions were produced.